A Review on Shunt Active Power Filter Control Strategies - Singh, Harnek; Kour, Maneet; Vinod Thanki, Dip; Kumar, Prakash (International Journal of Engineering and Technology, 2018)
Shunt active power filter (SAPF) has now become a well-known sophisticated technology to overcome current harmonics and reactive power compensation issues. In this paper a technical review of various control strategies for operation of SAPF has been presented. Control strategies such as reference current generation by time domain, frequency domain and soft computing approaches; voltage control for dc link voltage regulation and current control for generating switching patterns for voltage source inverter has been discussed. This paper aims to provide a broad understanding on SAPFs for various research and engineering applications.Â Â